The Use of Science Technology In Islamic Practices and Rules In The Past Now and The Future - Desy Apriani; Alexander Williams; Untung Rahardja; Alfiah Khoirunisa; Sella Avionita (International Journal of Cyber ​​and IT Service Management (IJCITSM), 2021)
Civilization is a complex structure of society characterized by urban development, social stratification applied by cultural elites, systems symbolic communication (eg, writing systems), and the perceived separation from and domination over the natural environment. Islamic civilization is a civilization that is built on basic Islamic aqidah, aims according to the purposes (maqashid) of sharia, and is realized by imitating the deeds (sunnah) of the Prophet Muhammad, his companions and the signs signs of halal and haram. Islam was at the pinnacle of civilization when the Khilafah system was still upright, despite the ups and downs. Based on Islamic ethics, In the case of virtue seeking new knowledge, it is achieved as a result of moderation of two extreme biases namely, avoiding acquiring new knowledge but remaining in a position of ignorance and playing an important role in pursuing ignorance. Thus, the ethics of Islamic knowledge, which is the application of science and technology science in Islam must be regulated, striving to free humans from these two negative tendencies. The core idea discussed in this paper is the science design used with special reference to Science and Technology. In the history of Islamic thought, this concept is articulated mainly in the background of cognitive psychology theory and Maqashid ash-sharia (a higher goal than Sharia) which is connected to the search for personal and social knowledge. Muslims are now able to pave the way for creating more advanced scientific and technological habits in twenty-first century Muslim societies.